Smartphone application: useful tool in hand hygiene adherence control - Basso, Eduardo Signor; Spall, Barbara; Roth, Eduarda Stopiglia; Krummenauer, Eliane Carlosso; Menezes, Rochele Mosmann; Koepp, Janine; Machado, Janete Aparecida Alves; Reuter, Cezane Priscila; Carneiro, Marcelo (International Journal of Infection Control, 2020)
This study analyzed hand hygiene adherence based on the direct observation computed through a standardized electronic form (Google forms®) available in an smartphone. The observed monthly adherence rates increased during the period. The frequency rates were 21.3% in September; 33.3% in October; 38.7% in November; and 59.7% in December (p <0.001). The introduction of direct observation through an smartphone facilitated the strategies and provided periodic feedback.